Patients' choice preferences for specialist outpatient online consultations: A discrete choice experiment - Wu, Mengqiu; Li, Yuhan; Ma, Chengyu (Frontiers in Public Health, 2023)
Background: Internet hospitals are multiplying with solid support from the Chinese government. In internet hospitals, specialist outpatient online consultations (SOOC) are the primary services. However, the acceptance and utilization rates of this service are still low. Thus, the study of patients’ choice preferences for SOOC is needed. Objective: To analyze the choice preference of patients’ SOOC via a discrete choice experiment, understand the influence of each factor and promote the development of internet hospitals. Methods: Via a discrete selection experiment, a total of 162 patients from two general hospitals and three specialized hospitals in Beijing were selected for the questionnaire survey. The choice preferences were analyzed by conditional logit regression. Results: From high to low, patients’ willingness to pay (WTP) for the attributes of SOOC is as follows: doctors’ recommendation rate (β highly recommend=0.999), the convenience of applying SOOC services (β convenient=0.760), the increasing ratio of medical insurance payment for online services compared to offline (β increased by 10%=0.545), and the disease’s severity (β severe=-3.024). The results of the subgroup analysis showed differences in patient choice preference by age, whether the patients had chronic diseases, income, and medical insurance types. Conclusion: Both price and nonprice attributes influence the choice preference of SOOC for patients. Among them, patients are more inclined to choose SOOC when doctors highly recommend it, when it is convenient to apply, when medical insurance increases by 10%, and when disease severity is mild. The current findings show the government and medical institutions formulate auxiliary policies and welfare strategies by clarifying core attributes and adjusting the levels of different attributes to improve patients’ acceptance with SOOC. The utility of SOOC and further development of internet hospitals are radically promoted.